Chemical characterization of Siraitia grosvenorii granules and their efficacy and mechanism of action on PM2.5-induced acute lung injury - Qi Shao; Yan Zhao; YuYu Shi; Fafeng Cheng; ZeHan Zhang; Ying Liu; ChangXiang Li; ZiLin Ren; Hua Bai; Haojie Cheng; Rolando Maddela; Junqiang Tian; et al. (Ecotoxicology and Environmental Safety)
This study aimed to investigate the potential protective properties of a traditional Chinese medicine (TCM) herbal product, Siraitia grosvenorii granules (SGG) against PM2.5-induced lung injury, as well as their active constituents and underlying mechanisms. The chemical composition of SGG, such as wogonin (MOL000173), luteolin (MOL000006), nobiletin (MOL005828), naringenin (MOL004328), acacetin (MOL001689), were identified via ultra-high-performance liquid chromatography-Q Exactive (UHPLC-QE) Orbitrap/MS. The specific targets and pathways through which the compounds exert their effects on acute lung injury were then predicted via network pharmacology. The lung-protective effects of SGG against particulate matter (PM2.5) were investigated via in vivo experiments. Results showed that PM2.5-induced lung damage was associated with oxidative stress, suppression of PI3K/AKT/Nrf2 pathway, and increased levels of certain alarmins & cytokines in blood and bronchial alveolar lavage fluid (BALF). However, SGG reversed these changes, particularly tissue damage and oxidative stress, suggesting that lung protection is mediated by the antioxidant effect, which mitigates the release of alarmin and inflammation.